Assification of Interactive Multimedia-Based Teaching Materials in Class VIII Culture Arts - Iskandar Muda; Uyuni Widiastuti; Suharyanto (Britain International for Academic Research (BIAR) Publisher, 2022)
The title of the research is Asification of Interactive Multimedia-Based Teaching Materials in Class VIII Arts and Culture Subjects. The background of this research is that there is no material available for Class VIII Cultural Arts subjects (especially music and dance materials) that use interactive multimedia. The objectives of the research were: to compile teaching materials for the art of music and dance based on interactive multimedia in the Class VIII Cultural Arts learning in the form of a Book Creator. The target achieved in this research is to produce interactive multimedia teaching materials which are integrated into a single unit in the form of a Book Creator. The results of the study resulted in Cultural Arts teaching materials in the form of Book Creator consisting of e-books (materials for the art of music and dance), Malay music learning videos on Sri Langkat songs and techniques for playing Malay musical instruments, and Nias dance learning videos on Giri-giri dance and Nias dance techniques. It is hoped that the existence of Cultural Arts teaching materials using interactive multimedia (Book Creator) can increase students' creativity in learning Cultural Arts.